Aesthetic matters: writing and Cultural Studies. Issue 2 (4th March 2018) - Highmore, Ben
ABSTRACT: What would it mean to treat Cultural Studies as a project that has had amongst its accomplishments the production of new forms and styles of writing, and a generative approach to aesthetics? An initial answer to this question would be that this would recognize how Cultural Studies interceded in an academic environment not only through its concern with supplying ambitious questions and insisting on a broad range of objects of scrutiny, but also by showing how this often entailed reconfiguring the forms through which intellectual inquiry conveyed its cargo. This article doesn't seek to provide a taxonomy of Cultural Studies' forms and styles; what it seeks to do is to encourage a self-reflexive attention to aesthetics within Cultural Studies as a form of practice. It suggests that there are two guiding questions that might frame such an attention: how might Cultural Studies generate forms that are adequate to the complexity of the configurations that it seeks to register; and how might Cultural Studies generate forms that could reach the ear of new audiences not attuned to the cadences of scholarly writing? The tension between these two questions should be seen as an invitation to purposeful experimentation within Cultural Studies.